2007
DOI: 10.1002/jmr.866
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical and single molecule force spectroscopy studies of specific interaction between the laminin binding protein and the West Nile virus surface glycoprotein E domain II

Abstract: ELISA and Western blot immunochemical data attest an effective and highly specific interaction of the surface glycoprotein E domain II (DII) of the tick born encephalitis and Dengue viruses with the laminin binding protein (LBP). Based on a highly conservative structure of the DII in different flaviviruses we propose a similarly effective interaction between the LBP and the DII of the surface glycoprotein E of the West Nile virus. We report the results of studies of this interaction by immunochemical and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…We found that laminin bound to the dengue envelope protein, and several laminin binding proteins and receptors have already been suggested to act as receptors or cofactors for both dengue and West Nile virus entry in mosquito and mammalian cells (Bogachek et al, 2008; Sakoonwatanyoo, Boonsanay, and Smith, 2006). This indicates that the TAP method can accurately identify host proteins known to bind components of the virion surface by using the envelope protein.…”
Section: Discussionmentioning
confidence: 76%
“…We found that laminin bound to the dengue envelope protein, and several laminin binding proteins and receptors have already been suggested to act as receptors or cofactors for both dengue and West Nile virus entry in mosquito and mammalian cells (Bogachek et al, 2008; Sakoonwatanyoo, Boonsanay, and Smith, 2006). This indicates that the TAP method can accurately identify host proteins known to bind components of the virion surface by using the envelope protein.…”
Section: Discussionmentioning
confidence: 76%
“…5). Ribosomal protein p40 [VectorBase: AAEL008083/AAEL013694] is a precursor of the high affinity laminin receptor, a putative receptor for the entry of DENV into host cells [25,47]. While mature laminin receptors are located on the cell surface, p40 has been detected in different compartments of cells, and is suggested to be a shuttle protein between the cytoplasm and the nucleus [48].…”
Section: Resultsmentioning
confidence: 99%
“…The same covalent attachment of proteins onto tip and sample surfaces without special linkers has been used in our previous force spectroscopy researches with WNV protein E (or its fragments) and its putative cell receptors (Bogachek et al ., , ). This similarity is very important for a direct comparison of the results obtained in these aforementioned works and in the present study.…”
Section: Methodsmentioning
confidence: 99%